Peran Manajemen dalam Meningkatkan Mutu Pendidikan Anak Usia Dini : Tinjauan Literatur - Ahyar Ahyar; Amanah Putri Fadillah; Fannia Sri Juwita (Lembaga Pengembangan Kinerja Dosen, 2025)
In the context of improving the quality of early childhood education, educational management plays a central role. Effective and efficient management is able to manage various existing resources optimally so as to create a conducive and quality learning environment. In addition, management is also responsible for designing learning programs that are in accordance with the needs of child development, supervising, evaluating, and providing training and professional development for educators. Thus, the role of management is not only administrative, but also strategic in improving the quality of early childhood education services. This research is a type of literature study. Library Research refers to a series of broad and systematic activities that are closely related to various sophisticated methodologies used in careful library data collection, comprehensive reading and accurate recording of relevant information, and complex processing of various research materials. Based on the results of the literature, the data collected shows that the role of management in improving the quality of early childhood education (PAUD) is very complex and multidimensional. The studies reviewed underline the importance of comprehensive planning, including the development of relevant curricula, the provision of adequate facilities and infrastructure, and the management of quality human resources. In addition, efficient organization, effective program implementation, and structured supervision have also been shown to contribute significantly to improving the quality of PAUD.